Nina Opanasivna Virchenko (on his 90th birthday) - Samoilenko , A. M.; Klesov , O. I.; Zaderei, P. V.; Nefedova , G. D.; Zaderei , N. M.; Gaidei , V. O. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
The article is devoted to the 90th anniversary of famous Ukrainian scientist. We are talking about professor of mathematics Nina Virchenko. We cover her tough life journey, scientific, educational and public work. Nina Virchenko devoted her life to Ukraine and mathematics.